Integration of Biomimicry Design Thinking And The Green Building Certification Systems: Leed as a Case Study - KARABETÇA, ALİYE RAHŞAN (My University, 2018)
21st century which is called Anthropocene age by scientist, also known as the age of modern man, has dramatically decreased the sustainable living conditions of planet earth. Each country whether developed or not, is struggling with the devastating effects of climate change, environmental pollution, decrease in non-renewable resources, etc. Thus, a demand for sustainable built environment has arose since the beginning of this age and it is growing every day. However, this demand is barely met by some initiatives which are dealing with the green building certification systems, such as Leadership in Energy and Environmental Design (LEED). It was established by united states green building council in 1993. It provides and encourages architects to design buildings that function more efficiently in terms of energy saving and lowering carbon footprint [1]. There are almost hundred thousand buildings all over the world using LEED and more than two million square meters certified every day including neighborhoods, existing buildings and new constructions [2]. Nevertheless, this certification system can be improved by integrating biomimicry design criteria into the requirements list that would develop specially the design stage of projects. This integration can lead designers to create energy efficient buildings which would decrease the impact of climate change on earth. Biomimicry is a new field of science that deals with transferring nature’s genius into man-made designs. It leads designers to use principles and strategies of functions of natural designs to solve human challenges. The main goal of both green building certification system and biomimicry is actually the same. Although biomimicry is for all fields, they both are required for better built environments. They aim to save and protect the nature; one is very limited in terms of specific parts of built environment, the other is very wide offering nature’s endless solutions to every part of built environment. This paper aims to study the methods and consequences of integration of biomimicry design thinking and green building certification system to develop a new design stage which would concentrate on logic of use of biology and basic requirements of certification criteria of LEED.
Keywords: biomimicry; green building; anthropocene; architecture sustainability